Risk-directed treatment intensification significantly reduces the risk of relapse among children and adolescents with acute lymphoblastic leukemia and intrachromosomal amplification of chromosome 21: a comparison of the MRC ALL97/99 and UKALL2003 trials. - Moorman, A; Robinson, H; Schwab, C; Richards, S; Hancock, J; Mitchell, C; Goulden, N; Vora, A; Harrison, C (2013)
PURPOSE: To evaluate the effect on outcome of intensifying therapy for patients with acute lymphoblastic leukemia (ALL) and an intrachromosomal amplification of chromosome 21 (iAMP21). PATIENTS AND METHODS: We report two cohorts of patients treated on Medical Research Council ALL97 or United Kingdom (UK) ALL2003. iAMP21 was identified retrospectively in ALL97 and was not used to guide therapy. However, in UKALL2003, iAMP21 was determined prospectively, and patients were allocated to the most intensive treatment arm (regimen C), which included augmented Berlin-Frankfurt-Munster consolidation, escalating Capizzi maintenance, double delayed intensification, and an option for first remission transplantation. The presence of iAMP21 was determined by fluorescence in situ hybridization using probes specific for the RUNX1 gene. RESULTS: iAMP21 was identified in 2% of patients with B-cell precursor ALL treated on UKALL2003 and ALL97. The event-free survival, relapse, and overall survival rates at 5 years for iAMP21 patients treated on ALL97 and UKALL2003 were 29% and 78%, 70% and 16%, and 67% and 89%, respectively (all P < .01). Patients treated on ALL97 had an increased risk of relapse compared with patients treated on UKALL2003 (hazard ratio, 7.2; 95% CI, 2.91 to 17.87; P < .001). CONCLUSION: iAMP21 patients with ALL benefitted from receiving more intensive therapy in UKALL2003. In UKALL2011, they will continue to be treated as cytogenetic high risk, receive intensive chemotherapy (regimen C), and will only be recommended for transplantation if they do not achieve a complete remission by the end of induction therapy. This study illustrates how the discovery and characterization of disease-specific genetic aberrations can be used to tailor therapy more precisely.